KESIAPAN GURU SENI BUDAYA DALAM PELATIHAN ONLINE DI ERA INDUSTRI 4.0. - Wuryaningsih (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
Industrial era 4.0. implies major changes in all aspects of life, especially in the field of education. Although web-based learning has been a major issue since the early of 21st century, digital skills are still emerging as a constraint. The global pandemic has abruptly pushed online training as an answer to sustainability within education. This study explores the readiness of teachers in online training in the new adaptation era. The research subjects were 187 art and culture teachers of junior, senior, and vocational high schools attended online training conducted by BBPPMPV Seni dan Budaya. The result of the study demonstrates significant achievement of teachers’ scores in the test. However, some conditions were recognized as teachers’ limitation during the online training, namely the access to the internet, the availability of tools and materials of skills practice, and their mastery of Google Classroom as learning management system. Teachers’ self-motivated action to join the online training and the increase of their post-test scores reveal their readiness for attending the online training. On the other hand, online training is not just an issue to learn something by the means of internet, but it is also critical to reflect on how to bring classroom experiences into the online platform by utilizing LMS features which support learning process itself